Investments to create bargaining power: the case of franchising - Michael, Steven C. (Strategic Management Journal, 2000)
Hybrid organizational forms such as franchise systems join two or more independent parties under a contract. The ability of each party to achieve its goals depend upon the relative bargaining power in the relationship established by the contract. Using transaction cost economics and Porter's (1980) characterization of sources of bargaining power, this paper argues that the franchisor can make investments in activities such as tapered integration and buyer selection to increase its bargaining power and decrease conflict and litigation in a franchise system. Specifically, tapered integration (owning some units while franchising others), selecting inexperienced franchisees, and employing a long training program are predicted to increase the franchisor's bargaining power and the franchisee's compliance with franchisor standards. An empirical analysis of litigation in restaurant franchise systems supports the theoretical hypotheses. Copyright © 2000 John Wiley & Sons, Ltd.